Study of Synthesis and Characterization of Pure Cus and Cufes Nanoparticles by Hydrothermal Method: Pharmaceutical Science-Nanoscience - Thilagavathi, L.; M. Venkatachalam, Dr.; M. Saroja, Dr.; Senthil, Dr.T.S. (International Journal of Life Science and Pharma Research, 2023)
Copper-based material has good electrical and optical properties but is not only physical properties and also good in antibacterial applications. Nano-structured CuS has potential value on high photocatalytic activity because of their suitable band gap and catalytic ability. CuS NP hydrogels had both adjustable physical properties and good injectable self-healing characteristics and excellent functionalities, concurrently including hemostatic ability, bacteria-killing capability, and cell migration and proliferation promotion. In vivo wound, healing, and histomorphological examinations of immunofluorescence staining in a mouse full-thickness wound model demonstrated good acceleration effects of these hydrogels for infected wound healing. A novel Chalcopyrite CuFeS nanocrystals are used as a Fenton reagent to degrade organic dyes without any additional source efficiently. Subsequently, the CuFeS2 nanocrystals/ biomass composite degradation column is made, continually degrading organic dyes. This paper demonstrates a comparative study of the synthesis and characterization of pure CuS and CuFeS nanoparticles using copper chloride, thiourea, ferric chloride and water solvent by straightforward hydrothermal methods. The synthesized material was characterized by an Xray diffraction (XRD), Scanning Electron Microscope (SEM), and Energy Dispersive X-ray spectrum (EDAX) techniques employed to study the nanostructure properties of the prepared sample. Crystallite size was determined by the Debye-Scherrer formula and found to be 15.5 nm and 20.55 nm, respectively. The EDAX spectrum showed a clear peak of present elements. An SEM image shows the morphology of the nanostructures. Optical analysis was done with UV and FTIR techniques. The pure CuS and CuFeS synthesized Tauc Relation and calculated nanomaterials bandgap came out to be 4.6eV and 4.4 eV, respectively.